Sri Vishnu sahasranama : with the bhashya of Sri Parasara Bhattar : with translation in English - Parāśarabhaṭṭa, 1017-1137 (Sri Visishtadvaita Pracharini Sabha, 1983)
Viṣṇusahasranāma, a hymn to Vishnu from the Mahabharata, lists his 1000 names.